جريمة التشهير عبر وسائل التواصل الاجتماعي في نظر القانون الوضعي الإندونيسي والشريعة الإسلامية - Dwi Pramono (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2022)
This research aims to clarify the crime of defamation through social media from the perspective of the Information and Electronic Transactions Law (UU ITE) and Islamic Sharia. In his study, the researcher followed the analytical and inductive approach that relies on the Qur’an, the Sunnah, the Criminal Law (KUHP) and the Law of Information and Electronic Transactions (UU ITE), and studies and reports that focused on such a topic, which were obtained from primary and secondary sources. Among the most important findings that the researcher pointed out is that Islamic law considers defamation a criminal act with different types of acts such as slander, cursing, insulting, humiliation, and so on. Its evidence is the recognition or presentation of witnesses, directly or indirectly. Moreover, the punishment that can be inflicted is in the form of the main punishment which is eighty beatings for slander and reprimand for other crimes. As for the Indonesian positive law, defamation in its texts is considered a crime of consideration that affects a person in his honor and his honor, either verbally or in writing, or legally punishable images, the Information and Electronic Transactions Law (UU ITE) and the Criminal Code (KUHP). The evidence and its completeness, and the punishment depends on the type of crime committed.